Climate Change Policy Evaluation and Its Impact on Island Nations: Case Of Singapore And Sri Lanka (International Journal of Built Environment and Sustainability, 2019)
Climate Change (CC) is universally recognized as a major global threat due to its nature of impacts. Island nations are known to be the most vulnerable to CC impacts where many countries have initiated mitigation and adaptation actions through sector-based policy measures. Singapore and Sri Lanka are two Asian island nations with CC induced threats. Two countries are different in terms of economic development, but similar developing countries in the CC agenda. In this context, both the countries have initiated mitigation and adaptation actions through policy measures. This study compares the key climate driven performance indicators with historical data to evaluate the performance of climate change policy of each country. Generally, policy evaluation has been conducted by adopting scientific and non-scientific tools, but it is seldom see that the relation of climate driven indicators along with CC policy. Also the policy research was mostly based on European case studies and Asian island nations were not easy to find in this context. The comparison of two countries in terms of CC policy is to determine the key vulnerable sectors where intervention is necessary for island nations. Mitigation policies are evaluated in Singapore and Sri Lanka using GHG emission pathways under twelve (12) indicators and adaptation policies are measured under the national expenditure of key sectors of the economy under seven (07) indicators. The analysis further elaborated by comparing both countries with key economic sectors that has positive and negative influence on CC impacts. Finally, the analysis outcome is used for lessons to learn from each other in improving the CC policy of Singapore and Sri Lanka. As every country has a unique set of strategies to minimize contributions to CC impacts, unique features that are common to both countries are chosen as variables for the comparison. Policy recommendations are provided to implement solid action plan for post 2020. The study expects to assist island countries to strengthen the CC policy as a national priority to manage unforeseen impacts posed by CC phenomena
Keywords: Climate Change; Island Nations; Policy Evaluation; Mitigation; Adaptation.